Comparison of low load blood flow restriction and high load resistance training of the finger flexors in advanced level climbers: a pilot study - Andersen, V.; Hermans, E.; Hansen, K. G.; Solstad, T. E. J.; Saeterbakken, A. H.; Balas, J.; Paulsen, G.; Stien, N. (Frontiers in Physiology, 2026)
Introduction: The aim of the present pilot study was to compare the effects of low load blood flow restriction (LL-BFR) with high load resistance training (HL) in advanced level climbers.